(untitled) - Burdge, Julia (Boston, 2009)
Chemistry, First Edition, by Julia Burdge has been created to bridge the gap in the McGraw-Hill general chemistry offerings. This textbook offers a clear writing style written with the students in mind. Julia uses her background of teaching hundreds of general chemistry students per year and creates content to offer more detailed explanation on areas where she knows they have problems.
Hóa học đại cương 1
Keywords: Chemistry,Hóa học